Law No. 2 of the year 2018: Promulgating the Law on the Comprehensive Health Insurance = قانون نظام التأمين الصحي الشامل - Egypt (2025)
Part-1: Definitions and Scope of application Part-2: Management of the scheme Chapter - 1: General organization for comprehensive health 12 insurance 12 Chapter - 2: General Organization for Health Care Chapter 3: General Organization for Accreditation and Health 61 Control Part -3: Sources of finance Chapter - 1: Sources of Finance of the Organization Chapter - 2: Sources of Finance of the National Healthcare Organization Chapter - 3: Sources of Finance of the General Organization for Accreditation and Health Control 42 Part-4: 44 Part-5: Penalties Table (1) Premiums of the Insured and Dependents ES Table (2) Share of Employers for their Employees Table (3) Charges and Copayments of Insured person Table (4) Obligations of Public Treasury for the Poor 55 Table (5) Phases of Application of the Comprehensive Health Insurance